MICROBIAL TRANSFORMATION OF ARYLPROPANOID CINNAMALDEHYDE BY THE PHYTOPATHOGEN FUNGUS Colletotrichum acutatum - CORREA N., Yaned M.; DURANGO R., Diego L.; GARCÍA P., Carlos M. (Vitae, 2009)
Phytopathogenic fungi have the capacity to modify chemically a wide array of organic compounds turning them into structurally related products. In this study, biotransformation of the substrate arylpropanoid trans-cinnamaldehyde A achieved by the phylamentous phytopatogenic fungus Colletotrichum acutatum, is evaluated; the process is carried out in liquid media culture Czapeck-Dox. The biotransformation of the substrate A produces the metabolites cinnamyl alcohol B, 3-phenyl-1-propanol C, 3-phenyloxiranemethanol D and 1-phenyl-1,3-propanediol E. The structures of metabolic products are determined by gas chromatography coupled with mass spectrometry (GC-MS) and nuclear magnetic resonance of proton and carbon (1H and 13C NMR). The process is marked by the tendency of the pathogen to produce hydroxylations on the substituent of the aromatic ring. Additionally, it has the capability to reduce the carbonyl group and the double bond. In the process, several metabolic products used like raw materials for different industries are generated. A possible metabolic pathway of the biotransformation of transcinnamaldehyde by C. acutatum is also discussed.